(untitled) (Veterinary Science, 2024)
Antibiotics are one of the potential contaminants in milk. The application of these pharmacological treatments generates residues that can persist for a longer or shorter time, in treated animals and in processed products. The aim of this study was to determine the presence of antibiotic residues in raw and pasteurized bovine milk from dairy farms of Lerma Valley basin in Salta. From 10 dairy farms, milk samples were taken from both the cooling tank and from15 random cows, prior to milking and after the cleaning routine. Milk Samples were also taken from 17 sachets from different commercial brands. The standard qualitative test Delvotest® SP NT was used for the determination of antibiotics. Of 150 milk samples obtained, 30 were positive for the presence of antibiotics, which represents 20% of the total evaluated. A similar percentage (2/10) was detected in samples from the cooling tank. All commercial milk samples were negative for the presence of antibiotics. The results of this study indicate that there are dairy farms where the use of these products is carried out without considering the recommended withdrawal times and that the milk from treated animals is stored together with the milk obtained from the rest of the herd. Also, that the milk which is consumed by the population would not represent any risk regarding the ingestion of antibiotic residues.